Artificial Intelligence (AI) in Ayurveda: Its Application and Relevance - Sanjay Gupta; Narasimha V; Vijaya Lakshmi A (AYUSHDHARA, 2025)
As the world develops, people are becoming increasingly obsessed with modern technology. Every system, including healthcare, is adapting to this trend, particularly through the use of Artificial Intelligence (AI) to provide quick, easy, and convenient services. The Ayurveda system of medicine, an ancient practice originating over 5,000 years ago, is inherently holistic and individualized, focusing on the balance of body, mind, and spirit. This article aims to investigate where and how AI can be integrated into Ayurveda and to what extent it can support Ayurvedic physicians. Various research articles and classical Ayurvedic texts were reviewed, and expert opinions were gathered for this analysis. The integration of AI into Ayurveda represents a transformative approach to traditional medicine, offering innovative solutions for diagnosis, treatment, and personalized healthcare. With its advanced data analytics, machine learning, and predictive modelling, AI can enhance the understanding and application of Ayurvedic principles. By analysing vast amounts of historical and contemporary data, AI can assist in identifying patterns in patient health, predicting disease susceptibilities based on Prakriti (body constitution), and optimizing personalized treatment plans. Additionally, AI-driven tools can support the discovery of new herbal formulations and their applications, thus expanding the scope of Ayurvedic treatments. The synergy between AI and Ayurveda holds the potential to revolutionize healthcare by merging ancient wisdom with modern technology, ultimately leading to more effective, personalized, and preventive healthcare solutions.